The impact of foliar applied zinc fertilizer on zinc and phytate accumulation in dorsal and ventral grain sections of four thai rice varieties with different grain zinc - Pennapa Jaksomsak (2018)
© 2017 Elsevier Ltd This study investigated the effect of foliar applied zinc (Zn) on the distribution of Zn and phytate in rice grain between four Thai rice varieties that differ in grain Zn. Foliar Zn application at 0.5% ZnSO 4 was applied at flowering and the early milky stage compared with non-foliar applied Zn. Among the high-yielding, low grain Zn varieties (CNT1 and RD21), foliar applied Zn increased Zn concentration in both dorsal and ventral sections of unpolished rice by up to 17.7 and 14.3%. In the low-yielding, high grain Zn varieties (KPK and NR), Zn concentration increased by 11% in the dorsal section of NR, but no effect was found in both sections of KPK. In polished rice, the Zn concentration increased by 20% in both sections but it was increased only in the ventral section of KPK and CNT1 by 21.0% and 25.0% respectively, while there was an increase of 12.5% in the dorsal section of RD21. The phytate in the seed fractions was measured as an indication for Zn bioavailability within humans. A lower phytate concentration was observed after foliar Zn application in both unpolished and polished rice, indicating the potential for a higher bioavailability of Zn in the rice grain.